Reproducibility of the Brazilian version of the Edmonton Frail Scale for elderly living in the community - Suzele Cristina Coelho Fabrício-Wehbe; Idiane Rosset Cruz; Vanderlei José Haas; Marina Aleixo Diniz; Rosana Aparecida Spadoti Dantas; Rosalina Aparecida Partezani Rodrigues (Universidade de São Paulo, 2013)
OBJECTIVE: to verify the inter and intra-rater reproducibility of the Brazilian adapted version of the Edmonton Frail Scale (EFS) in an elderly group of residents. METHOD: in order to test the inter-rater reproducibility, two assessments were independently conducted by two researchers on the same day but at different times, in a sample of 103 elderly. Concerning the intra-rater reproducibility, the instrument was administered to 83 elderly (80.6% of the initial sample) by the same researcher in a time gap of 15 days between the two assessments. RESULTS AND DISCUSSION: in relation to the inter-rater test, the Kappa was 0.81 (CI 0.61-1.00) and the Intraclass Correlation Coefficient (ICC) corresponded to 0.87 (CI 0.82-0.91, p<0.001). In relation to the intra-rater test, the Kappa was 0.83 (CI 0.72-0.94) and the ICC 0.87 (CI 0.81-1.00, p<0.001). CONCLUSION: the results show that the EFS is reliable and can be used as a tool to improve geriatric nursing care in Brazil.